Revitalisasi Tradisi Sedekah Bumi: Strategi Rekayasa Sosial dalam Memperkuat Solidaritas Masyarakat Cirebon - Maulidyah Nur Indah Putri; Ghina Syahira Idham; Muhammad Abror Amanullah (Jurnal Artefak, 2025)
The Sedekah Bumi tradition in Cirebon is a local cultural practice rooted in agrarian life and transmitted across generations as an expression of gratitude for agricultural harvests as well as a means of social integration. However, in the current social context, this tradition faces challenges such as declining community participation, cultural commodification, and the erosion of traditional values under the pressure of modernization. This study aims to examine how the revitalization of Sedekah Bumi functions as a form of social engineering to strengthen community solidarity and social resilience. This research employs a qualitative descriptive method through a literature-based approach that analyzes scholarly sources on local traditions, social capital, and social engineering. The findings show that revitalization not only restores the cultural function of the tradition but also reinforces social ties through collective participation, community cooperation, and the preservation of local values. Through this process, Sedekah Bumi has transformed from a cultural ritual into a strategic social instrument capable of maintaining social cohesion amid societal changes. The novelty of this study lies in its emphasis on positioning local tradition not merely as a cultural heritage to be preserved but as an adaptive social strategy for strengthening community resilience.